Quantitative real-time RT-PCR and chromogenic in situ hybridization: precise methods to detect HER-2 status in breast carcinoma - Rosa, Fabiola E. [UNESP]; Silveira, Sara M. [UNESP]; Silveira, Cassia G. T. [UNESP]; Bergamo, Nadia A. [UNESP]; Moraes Neto, Francisco A.; Domingues, Maria Aparecida Custódio [UNESP]; Soares, Fernando A.; Caldeira, Jose R. F. [UNESP]; Rogatto, Silvia Regina [UNESP] (Biomed Central Ltd., 2009)
Background: HER-2 gene testing has become an integral part of breast cancer patient diagnosis. The most commonly used assay in the clinical setting for evaluating HER-2 status is immunohistochemistry (IHC) and fluorescence in situ hybridization (FISH). These procedures permit correlation between HER-2 expression and morphological features. However, FISH signals are labile and fade over time, making post-revision of the tumor difficult. CISH (chromogenic in situ hybridization) is an alternative procedure, with certain advantages, although still limited as a diagnostic tool in breast carcinomas.Methods: To elucidate the molecular profile of HER-2 status, mRNA and protein expression in 75 invasive breast carcinomas were analyzed by real time quantitative RT-PCR (qRT-PCR) and IHC, respectively. Amplifications were evaluated in 43 of these cases by CISH and in 11 by FISH.Results: The concordance rate between IHC and qRT-PCR results was 78.9%, and 94.6% for qRT-PCR and CISH. Intratumoral heterogeneity of HER-2 status was identified in three cases by CISH. The results of the three procedures were compared and showed a concordance rate of 83.8%; higher discordances were observed in 0 or 1+immunostaining cases, which showed high-level amplification (15.4%) and HER-2 transcript overexpression (20%). Moreover, 2+ immunostaining cases presented nonamplified status (50%) by CISH and HER-2 downexpression (38.5%) by qRT-PCR. In general, concordance occurred between qRT-PCR and CISH results. A high concordance was observed between CISH/qRT-PCR and FISH. Comparisons with clinicopathological data revealed a significant association between HER-2 downexpression and the involvement of less than four lymph nodes (P = 0.0350).Conclusion: Based on these findings, qRT-PCR was more precise and reproducible than IHC. Furthermore, CISH was revealed as an alternative and useful procedure for investigating amplifications involving the HER-2 gene.